PENERAPAN METODE PEMBELAJARAN AKTIF TIPE THE LEARNING CELL MENGGUNAKAN MEDIA KARTU SOAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM KELAS X SMAN 1 PASIR PENYU - Eni Nur Rahmawati Rasmiwetti2, Rini3 Nur Rahmawati; Rasmiwetti '; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research aims to increase student achievementon the subjectstructure atomicinclassXSMAN 1 Pasir Penyu.  This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMAN 1 Pasir Penyu.The samples of this research were the students of class XMIA 3 as the experimental class and  students of class X MIA 1 as  the control class.Experimental class is a class that is applied active learning method The Learning Cell, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 3,24> 1,67, means that the application of active learning method The Learning Cell can improve student achievement on the subject of Structure atomicin class X MIA 3 SMAN 1 Pasir Penyu, increase learning of 14,5%. Keywords: Active Learning, The Learning Cell,card question.